1939
DOI: 10.1104/pp.14.2.297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heavy and Late Applications of Nitrogenous Fertilizer on the Cold Resistance of Kentucky Bluegrass

Abstract: IntroductionThe conditions under which turf-forming grasses on lawns and recreational fields are maintained are highly exacting. This is due chiefly to frequent and often close defoliation. On golf courses and athletic fields the situation is further aggravated by much trampling. To maintain a good sward under such adverse conditions resort is often made to liberal use of fertilizer. In order to take full advantage of the cool growing weather of late autumn and early spring, top-dressings are often made in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1943
1943
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…The grasses were permitted to hardeln naturally. Previous work (7) had shown that air temperatuires near the freezing point were necessary to harden turf grasses. That nlitrogen treatments may affect the degree of hardening of turf grasses to cold was showni by CARROLL and WELTON (7).…”
Section: Soil Droughtmentioning
confidence: 99%
See 4 more Smart Citations
“…The grasses were permitted to hardeln naturally. Previous work (7) had shown that air temperatuires near the freezing point were necessary to harden turf grasses. That nlitrogen treatments may affect the degree of hardening of turf grasses to cold was showni by CARROLL and WELTON (7).…”
Section: Soil Droughtmentioning
confidence: 99%
“…It should be noted that weather coniditions previous to these tests were not conducive to hardening to drought. In tests conducted on P. pratensis in 1930 and 1931, however, whenl weather conditions favorable to hardening to drought prevailed, CARROLL and AVELTON (7) founld a lack of correlation between bouncld w-ater content and drought hardiiness in low-and high-nitrogen grass.…”
Section: Soil Droughtmentioning
confidence: 99%
See 3 more Smart Citations